Assessing English Needs for Vocational Animal Feed Technology Students - Pratiwi, Gadis Kartika; Oktaviani, Eva; Mujianto, Gigit (Journal of English for Academic and Specific Purposes (JEASP), 2025)
This study investigates the English language needs, perceptions, and learning preferences of students in the Animal Feed Technology program at Politeknik Pertanian Negeri Kupang, located in Eastern Indonesia. Recognizing the region’s limited access to quality education and its impact on English proficiency, the research aims to answer three core questions: (1) What are the students’ English language needs and wants? (2) How do they perceive their academic and professional English requirements? (3) What are their preferred learning methods, materials, and classroom environments? Further, mixed-methods approach was employed, involving 97 student respondents who completed a structured questionnaire and seven students who participated in a focus group discussion (FGD). The findings reveal that most students self-identify as beginners in English, rarely use the language in academic contexts, and lack confidence in their communicative abilities. Despite these challenges, they are highly motivated by future career aspirations, identifying speaking, technical writing, and vocabulary development as crucial language skills. Students prefer multimedia and contextualized materials and favor collaborative and hands-on learning environments. The results highlight a significant gap between students’ current English proficiency and the demands of their academic and professional contexts. Based on these findings, the study recommends the development of an English for Specific Purposes (ESP) curriculum tailored to Animal Feed Technology, emphasizing functional communication, practical application, and learner-centered instruction. This research contributes to the literature on vocational ESP and provides actionable insights for educators and policymakers aiming to improve language education in underrepresented regions.